Analisis Scientometric Pendidikan Islam di Universitas Studi Bibliometrik Dengan Menggunakan R Biblioshiny - Amri Saputra (STAI Asy-Syukriyyah, 2026)
This study aims to map the development of Islamic education research at the university level during the period 2013–2025 using a scientometric approach with the R Biblioshiny tool. The research is motivated by the growing number of publications on Islamic education covering curriculum, teaching methods, Islamic values integration, and pedagogical innovation. However, most studies remain thematic or case-based, offering limited insights into broader research trends. Data were retrieved from the Scopus database using the keyword “Islamic education” and related terms, restricted to journal articles. The dataset was analyzed with the Bibliometrix package through the Biblioshiny interface. The analysis included annual publication trends, average citations per article, the most influential authors and journals, contributions from productive institutions and countries, collaboration networks, and keyword evolution. The findings reveal that Indonesia dominates global output, followed by Malaysia, Turkey, and several other countries. The dominant themes include Islamic education, higher education, curriculum, religious moderation, and teacher education. Visualizations through network analysis, word clouds, three-field plots, and treemaps demonstrate the clustering of themes and collaboration patterns, reflecting increasingly complex and multidimensional research directions. These results highlight the strategic role of Islamic higher education in shaping global discourse and emphasize the need for stronger international collaboration and interdisciplinary approaches to ensure that Islamic education research remains relevant and adaptive to contemporary challenges.